THE INFLUENCE OF THE APPLICATION OF TOTAL QUALITY MANAGEMENT OF EMPLOYEE PRODUCTIVITY AGAINST GIANT EXTRA MEGA BEKASI - Samosir, Octaviana Sarlinatua Samosir; Sidharta, Juaniva (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
Intense competition would demand the company to provide quality products to the consumer. But the attention the company is not limited to the quality of the resulting product, but also on aspects of the process, the human resources (HR) and the environment. Giant hypermarket is a retail company in Indonesia which is facing competition in retail business which rapidly, one way that's done to Giant hypermarket compete by implementing Total Quality Management (TQM), through the continuous improvement of product, labor, and the environment. TQM is a system achieve the objectives of the Organization, one of them an increase in employee productivity. Keywords : the application of total quality management, the influence of the application of total quality management, factors in influencing the success.